SEG Technical Program Expanded Abstracts 2000 2000
DOI: 10.1190/1.1815725
|View full text |Cite
|
Sign up to set email alerts
|

Seismic monitoring of CO2injected into a marine acquifer

Abstract: Statoil has injected CO2 into a saline aquifer for disposal. Monitoring the behaviour of the CO2 in the sand formation and the sealing capacity of the overlying shale cap rock are key elements in understanding the dynamics of the injection process. A repeated 3D seismic dataset was therefore acquired in 1999, after injection of about 2 million metric tons of CO2. The time-lapse data show a large increase in reflectivity and a large push-down of reflections caused by the injected CO2. Gas at different levels wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 1 publication
(1 reference statement)
2
29
0
Order By: Relevance
“…They are visible on all station combinations and on all components. The injection of CO 2 into a porous layer changes the medium and lowers the seismic velocities with respect to a reference state before the injection (Eiken et al 2000;Kazemeini et al 2010;Ivanova et al 2012). Therefore, we expect a monotonic decrease of the seismic velocities over the period of the injection because the injection is almost continuous with a constant rate (on average).…”
Section: Discussionmentioning
confidence: 99%
“…They are visible on all station combinations and on all components. The injection of CO 2 into a porous layer changes the medium and lowers the seismic velocities with respect to a reference state before the injection (Eiken et al 2000;Kazemeini et al 2010;Ivanova et al 2012). Therefore, we expect a monotonic decrease of the seismic velocities over the period of the injection because the injection is almost continuous with a constant rate (on average).…”
Section: Discussionmentioning
confidence: 99%
“…Modeling showed that the presence of gas induces a dramatic decrease of the P-wave velocity even for moderate CO 2 saturation, and consequently impacts the Top Utsira Formation reflection coefficient. 25% CO 2 saturation doubles the reflected amplitudes, while 100% gas saturation triples the reflected amplitudes (Eiken et al, 2000). Another seismic indication of the subsurface properties due to gas injection is the measured velocity pushdown determined by crosscorrelating the seismic traces between the baseline and the different monitoring surveys.…”
Section: Nrms (%)mentioning
confidence: 99%
“…The seismic images obtained highlight the strong effect of CO 2 injection on the seismic response, both on seismic amplitudes and traveltimes inside the CO 2 plume (Eiken et al, 2000).…”
Section: Case Study: the Co Storage Reservoir At Sleipner Sitementioning
confidence: 99%